Endoscopic Ultrasonography (EUS) Compared with Magnetic Resonance Cholangiopancreatography (MRCP) in Diagnosing Patients with Malignancy Causing Obstructive Jaundice - Kaka Renaldi; Rudy Kurniawan; Dadang Makmun (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Background: The common etiologies of obstructive jaundice were biliary stone and biliary neoplasms. The gold standard to diagnose malignancy causing obstructive jaundice is endoscopic retrograde cholangiopancreatography (ERCP) with sensitivity and specificity of 95% and 100%. However, ERCP is an invasive procedure associated with several complications such as bleeding, pancreatitis, and perforation. Other modalities include endoscopic ultrasonography (EUS) and magnetic resonance cholangiopancreatography (MRCP). Thus, we aim to evaluate the sensitivity and specificity of EUS with MRCP in patients with malignancy causing obstructive jaundice.Method: This was a cross-sectional study that calculates the sensitivity and specificity of EUS and MRCP in diagnosing malignancy causing obstructive jaundice compared with the gold standard, histopathology examination from ERCP. The study was conducted in the Medical Record Unit, Gastroenterology Division, Dr. Cipto Mangunkusumo National General Hospital, on January – March 2019 by using a consecutive sampling method. The date of diagnosis was collected from the medical record within five years. Subjects were selected based on inclusion criteria which include patients aged ≥ 18 years old who were diagnosed with malignancy causing obstructive jaundice by ERCP, and had underwent EUS or MCRP with a maximum interval of 3 months to ERCP. The exclusion criteria include patients with previous evidence of biliary tract malignancy or concurrent parenchymal jaundice. Statistical analysis was performed using IBM SPSS Statistics 20.Results: There were 54 subjects with a mean age of 56.48 ± 11.37 years. Subjects consisted of 29 (53.7%) males and 25 (46.3%) females. The median period between EUS to ERCP was 0-33 days, while MRCP to ERCP was 1-53 days. The sensitivity, specificity, positive predictive value, and negative predictive value to diagnose obstructive jaundice due to malignancy were 96%, 60%, 96%, 60% in EUS, and 90%, 40%, 94%, 29% in MRCP, respectively.Conclusion: EUS was more superior to MRCP in the diagnosis of  malignancy causing obstructive jaundice.